1995
DOI: 10.1159/000262101
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Chlorhexidine with Cytoplasmic Membranes of Streptococcus mutans GS-5

Abstract: Cytoplasmic membranes of Streptococcus mutans GS-5 were extracted by incubating cells with 1% sodium lauroyl sarcosinate for 20 min at room temperature. The profiles of membrane proteins were determined by SDS-PAGE and isoelectric focusing. The effect of chlorhexidine digluconate on cell membranes was studied after treating the extracted proteins for 30 min with the drug at final concentrations of 0.05 and 0.2%. Chlorhexidine caused selective reduction in the intensity of the membrane proteins. Five densely st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This suggests that in the zoocin A-and lauricidin-treated biofilms, the metabolic activity of S. mutans was compromised to a greater degree relative to cell death than in the chlorhexidine-treated biofilms, an effect that may relate to the mode of action of the respective compounds. Lauricidin and chlorhexidine both have the bacterial membrane as their primary site of action, however, while the positively charged chlorhexidine interacts directly with negatively charged membrane components [Koontongkaew and Jitpukdeebodintra, 1995], the neutrally charged lauricidin has been shown to also effect cytoplasmic targets including metabolism [Kabara, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in the zoocin A-and lauricidin-treated biofilms, the metabolic activity of S. mutans was compromised to a greater degree relative to cell death than in the chlorhexidine-treated biofilms, an effect that may relate to the mode of action of the respective compounds. Lauricidin and chlorhexidine both have the bacterial membrane as their primary site of action, however, while the positively charged chlorhexidine interacts directly with negatively charged membrane components [Koontongkaew and Jitpukdeebodintra, 1995], the neutrally charged lauricidin has been shown to also effect cytoplasmic targets including metabolism [Kabara, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…The chlorhexidine remains on the skin, providing an antimicrobial coating that is replenished with each bathing. Chlorhexidine is amphipathic, and it likely interacts with both phospholipids and proteins on the bacterial cell surface (15,16). Its interaction with the membrane is reported to be similar to that of antimicrobial peptides (15).…”
mentioning
confidence: 99%
“…Maisetta et al [20] showed that chlorhexidine might facilitate the access of human b-defensin 3 to the cytoplasmic membrane via damaging the outer bacterial membrane, which represents the main site of action. Similarly, Koontongkaew and Jitpukdeebodintra [21] found the effect of CHXD on cell membranes of Streptococcus mutans GS-5 after treating the extracted proteins for 30 min with the drug at final concentrations of 0.05% and 0.2% chlorhexidine caused selective reduction in the intensity of the membrane proteins. In addition, Kim et al [22] showed marked synergistic anti-bacterial effects of gaegurin 6 (GGN6), an animalderived cationic peptide, and its derivatives PTP6 and PTP12 with chlorhexidine on the growth of oral streptococci.…”
Section: Discussionmentioning
confidence: 84%